Human sperm DNA integrity : A difference of storage temperature and period of freeze-drying process - silvia werdhy lestari; ahmad silalahi; hamdani lunardi; agustinus agustinus (Journal of Global Pharma Technology, 2020)
The cryopreserve technique using liquid nitrogen is used to preserve human sperm. Nevertheless, this technique has several disadvantages, such as bacterial/viral contamination and its expensive cost. Freeze-drying process offers more simple and cheaper of sperm storage technique. This study aimed to investigate the effect of storage temperature and period of freeze-dried human sperm on DNA integrity. Human sperm samples of 15 donors were prepared with simple washing techniques. Post-washing samples (T0) were divided into 4 groups with the same volume. The four group of samples carried on the freeze-drying process and stored based on different temperature and period: 4°C for 1 week (T1), room temperature (24-25ºC) for 1 week (T2), 4°C for 3 months (T3), and room temperature for 3 months (T4). Sperm DNA integrity was analyzed before and after the storage period of each group. There was a statistically significant difference of sperm DNA integrity of freezes - dried at 4°C in 1 week versus 3 months (T1 vs T3), at room temperature in 1 week versus 3 months (T2 vs T4) (p